The impact of on-site cardiac surgical backup on clinical outcomes of acute coronary syndrome—analysis of the ACSIS national registry - Moady, Gassan; Ovdat, Tal; Rubinshtein, Ronen; Eitan, Amnon; Daud, Elias; Arow, Ziad; Atar, Shaul (Frontiers in Cardiovascular Medicine, 2023)
The availability of advanced technologies for mechanical support in hospitals with on-site cardiac surgery (CS), along with the ability to perform urgent coronary artery bypass graft (CABG) surgery, may result in improved clinical outcomes in patients with acute coronary syndrome (ACS).We conducted a retrospective analysis of the bi-annually Acute Coronary Syndrome Israeli Survey (ACSIS) registry from the year 2000 to 2020, performed in hospitals with and without CS. Mortality rates and major adverse cardiac and cerebrovascular events (MACCE) rates are reported. We evaluated two periods of the study -early (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) versus late (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020). Propensity score matching was performed to reduce bias between the two groups.The study included 16979 patients (52.3% in the on-site CS group). Patients in the on-site CS group were more likely to undergo percutaneous coronary intervention (PCI), (odds ratio [OR], 1.26 [95% CI, 1.18-1.35]; p<0.001) and CABG (OR, 1.91 [95%CI, 1.63-2.24]; P<0.001), and patients in hospitals without on-site CS had higher 30-day MACCE (OR, 1.17 [95% CI, 1.07-1.27]; p<0.0005). Overall, there was no difference in 1-year mortality (hazard ratio [HR], 0.98 [95% CI, 0.89-1.08]; p=0.71) between the groups. During the late period of the study, patients in the group 3 without on-site CS had lower 30-day mortality (OR, 0.69 [95% CI, 0.49-0.97]; P=0.04), yet with no difference in 1-year mortality (HR, 0.81 [95% CI, 0.65-1.01]; p=0.07).The availability of on-site CS resulted in variations in treatment modality, yet it did not affect the clinical outcomes of ACS. A trend to a better short-term outcomes was noted in hospitals without CS during the late period of the study, which warrants further investigation..